Effects of short range correlations on the Ca and O isotopes - Massen, S. E. (HNPS Advances in Nuclear Physics, 2020)
The effect of short range correlations on the Ca and 0 isotopes has been studied by using an isospin dependence of the harmonic oscillator spacing, hω and of the correlation parameter. The analysis indicates that short range correlations as well as the isospin dependence of the parameters are important to explain the behavior of the differences of the MS charge radii and the differences of the charge densities between the Ca and the Ο isotopes.